The Role of Packaging in Food Loss and Waste Reduction: A Mini Review from Indonesia - Derosya, Vioni; Ihsan, Taufiq (Jurnal Serambi Engineering, 2025)
This brief review highlights findings from research conducted in Indonesia, examining how packaging can play a crucial role in reducing food loss and waste within the supply chain. While the broader economic, social, and environmental ramifications of food waste are extensively covered in existing literature, this study specifically focuses on how innovative packaging solutions can mitigate food loss. In the realm of fresh produce, effective packaging not only preserves quality but also optimizes product protection, ventilation, and temperature regulation. The study explores several avenues for packaging improvements, including enhanced designs for distribution that reduce damage during transportation and handling, and consumer packaging innovations that help reduce household food waste by facilitating correct portion control and clarifying expiration date labeling. Furthermore, the adoption of pre-packaged goods is shown to streamline handling processes and improve inventory turnover in retail settings. A key insight from this research is that optimal waste reduction sometimes necessitates increased packaging use, highlighting the need for a holistic approach where packaging design is integrated thoughtfully with product needs to foster sustainability in the supply chain.